IMPLEMENTATION OF ISTISNAK CONTRACT IN HOUSEHOLD EQUIPMENT ‎BUYING TRANSACTIONS (CASE STUDY OF FURNITURE ENTREPRENEURS IN ‎POTOAN DAYA VILLAGE, PALENGAAN PAMEKASAN)‎ - Fata, Zainol (Islamic Economics And Finance Journal, 2023)
People in conducting transactions often do not know about the transactions being carried out. They carry out buying and selling transactions for household appliances in accordance with existing customs. It is the same with istisna' buying and selling contract transactions. In this study, the researchers focused on the problem of how the buying and selling system of household appliances is and how to apply the istisna contract to buying and selling household appliances in Potoan Daya Village, Palengaan Pamekasan. The researcher uses a qualitative approach, this type of research is descriptive, namely the data collected in the form of words and not numbers. In the research that has been done, the findings are based on the focus of the research, namely the system of buying and selling household appliances in Potoan Daya Village is in accordance with the provisions of the elements and pillars of buying and selling. The application of the istisna contract in the sale and purchase of household appliances in Potoan Daya Village is in accordance with sharia provisions because in the transaction the pillars and conditions have been fulfilled.